(untitled) - Hinton, Michael (U.K., 2005)
So many people know about the Bible but so few have read it at all, let alone from cover to distant cover. This version of the Bible has been written to bridge that gap. The 100-Minute Bible picks out the essential elements of the Bible from Genesis through to the Revelation of John using a universal language. Most people will be able to read it in 100 minutes, making it the ideal read for that upcoming rail or aeroplane journey, or for an enjoyable evening of enlightenment.
Keywords: Bible -- Paraphrases, English